2017
DOI: 10.21547/jss.290441
|View full text |Cite
|
Sign up to set email alerts
|

Merhametin Öznel İyi Oluş Üzerindeki Yordayıcı Etkisinin İncelenmesi

Abstract: ÖzetBu araştırma üniversite öğrencilerinin merhamet düzeylerinin öznel iyi oluş üzerindeki yordayıcı etkisini incelemeyi amaçlamaktadır. Çalışmada ayrıca öğrencilerin algılanan gelir düzeyi ile yerleşim yerinin merhamet ve öznel iyi oluş puanları üzerindeki etkisi ele alınmıştır. Araştırma grubunu 18-32 yaşları arasındaki 198'i kız (% 49.3), 204'ü erkek (% 50.7), toplam 402 öğrenci oluşturmaktadır. Araştırmada Merhamet Ölçeği, Öznel İyi Oluş Ölçeği ve Kişisel Bilgi Formu kullanılmıştır. Araştırma sonuçlarına g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
1
6
0
2
Order By: Relevance
“…As a result of the research, it was seen that there were positive and significant relationships between adults' compassion and their psychological well-being and life satisfaction and that compassion predicted psychological well-being and life satisfaction. Similar to our research results, studies have shown that compassion is associated with psychological well-being (Hutcherson et al, 2008;İşgör, 2017;Lutz & Skirberk, 2012) and life satisfaction (Hopkins & Reynolds, 2001;Ladner, 2004). Compassion arises when others are perceived as vulnerable, distressed, or needy, motivating the person to support others (Goetz et al, 2010).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As a result of the research, it was seen that there were positive and significant relationships between adults' compassion and their psychological well-being and life satisfaction and that compassion predicted psychological well-being and life satisfaction. Similar to our research results, studies have shown that compassion is associated with psychological well-being (Hutcherson et al, 2008;İşgör, 2017;Lutz & Skirberk, 2012) and life satisfaction (Hopkins & Reynolds, 2001;Ladner, 2004). Compassion arises when others are perceived as vulnerable, distressed, or needy, motivating the person to support others (Goetz et al, 2010).…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…In similar studies, Neff & Germer (2012) developed a self-compassion-based intervention program and found that the implemented program reduced stress and increased life satisfaction and quality. In addition, many studies have found a positive relationship between happiness and compassion (Erdoğan, 2017;Goleman, 2003;İşgör, 2017;Ladner, 2004;Lyubomirsky, 2008).…”
Section: The Mediator Role Of Compassion and Life Satisfactionmentioning
confidence: 99%
“…Gelir durumu yüksek olanlarýn, gelir durumu orta ve düþük olanlara göre paylaþýmlarýn bilincinde olma alt boyutu açýsýndan merhamet düzeylerinin düþük olduðu belirlenmiþtir. Ýþgör' ün (2017b) üniversite öðrencileriyle yaptýðý çalýþmada, çalýþmamýzýn aksine öðrencilerin merhamet düzeylerinin ailelerinin gelir düzeyiyle iliþkili olmadýðý tespit edilmiþtir (17). Çalýþmamýzdaki bu durum orta ve düþük gelirli öðrencilerin yaþamýþ olduklarý mutluluk veya sýkýntýlý deneyimleri ile ilgili empati kurarak baþkalarýna yardým etme konusunda daha istekli olmalarýndan kaynaklý olduðu söylenebilir.…”
Section: Gýrýþunclassified
“…CfO has been identified as a robust correlate of various phenomena such as problem-solving skills (Feher 2016), forgiveness (Arslan 2017), and body satisfaction (Vimalakanthan 2016). Of particular interest to the current investigation, CfO has also been associated with various indices of psychological well-being, including happiness and subjective well-being (Beaumont et al 2016a, b;Bibeau et al 2016;Demir 2017;İşgör 2017;Sanchez et al 2018). However, less is known about why the CfO-subjective well-being (hereafter SWB) relationship exists.…”
Section: Introductionmentioning
confidence: 91%